A simple method for developing efficient room temperature reduced graphene oxide-coated polyurethane sponge and cotton for oil-water separation. Issue 16 (2nd November 2022) - Zaidi, Shabi Abbas; Mohamed, Maimoona; Deyab, Nada
ABSTRACT: Oil spilled during transportation, domestic, and industrial usage causes grave water and soil pollution. Therefore, oil recovery through absorption or separation from water has been a challenge to the scientific community. The 3D porous structure of polyurethane (PU) sponge attracted significant attention in oil-water separation applications. However, its poor hydrophobicity decreases and limits its oil-absorption efficacy dramatically. In this paper, we focused on improving the hydrophobicity of the sponge by modifying it with graphene oxide (GO) followed by its reduction to reduce graphene oxide (rGO) via a commonly available green reducing agent, L-ascorbic acid (L-AA). The rGO modified PU sponge was used to absorb and collect oil from an oil-water mixture with satisfactory recoveries of up to 97%. Moreover, the prepared rGO-PU sponge exhibited excellent reusability and compressibility without any crack or leaking. Finally, we compared the results of this study with rGO modified cotton (rGO-cotton) surfaces prepared via the same protocols. The results show that the high compressible and porous nature of sponges (rGO-PU) outperformed the rGO-cotton. Furthermore, this research work was proven to be environmentally friendly and cost-effective absorbent for efficiently extracting oil from oil-water mixtures with fewer toxic chemicals and cheap raw materials utilization.